Load Cell Failure Risk in Tandem Mobile Crane Lifting: A Fuzzy Fault Tree Analysis Approach - Fatich Pradana Putra; Priyambodo Nur Ardi Nugroho; Imam Sutrisno (International Journal of Marine Engineering Innovation and Research, 2025)
Mobile crane lifting activities carry a significant accident risk, especially when performed in tandem configurations. The main risk comes from the possibility of failure of the load cell component which plays an important role in actual load measurement. This research aims to analyze the potential failure of the load cell function in tandem lifting operations using the Fuzzy Fault Tree Analysis (FFTA) method. Data were collected through literature studies, field observations, and interviews. The FFTA method is used to identify factors that cause failure and calculate the probability of failure quantitatively. The investigation identified that the primary variables leading to load cell failure include overload situations, internal component damage, and external impacts. The highest probability of failure was recorded in the material fatigue scenario due to damage to the cable. These findings highlight the need of instituting preventative maintenance programs and conducting frequent inspections of load cell components to reduce the risk of workplace accidents.